Community stakeholder perspectives for empowering EJ initiatives through Public Participation Geographic Information Systems (PPGIS) - Jacelyn Rice-Boayue; Laurie Garo; Elisabeth Ilboudo Nebie (Environmental Research Letters)
This study explores the use of Public Participation Geographic Information Systems (PPGIS) to support environmental justice (EJ) efforts in Charlotte, North Carolina by incorporating community knowledge and engagement. Through a workshop with representatives from community-based organizations (CBOs), participants learned about PPGIS, NASA remote sensing data, and environmental screening tools. A hands-on web-Geographic Information Science (GIS) demonstration allowed them to identify how PPGIS might address challenges in their EJ efforts. Using a mixed-methods approach, both surveys and focus group discussions were conducted to collect community and individual perspectives on the strategic implications of incorporating PPGIS into current EJ efforts. Thematic analysis of the focus groups revealed key themes of community engagement and representation, challenges with coordination, the power of GIS and data, political and policy advocacy, and holistic and intersectional approaches. Descriptive statistics and comparative insights from survey data revealed nuances in individual CBO representative’s perceived strengths, weaknesses, opportunities and threats, complementing focus group narratives. Assessment of the strengths, weaknesses, opportunities, and threats of current efforts showed that coalition building, community involvement, and local knowledge were key strengths. In contrast, weaknesses included a perceived lack of influence over decision-makers and difficulty securing funding. The study concludes that PPGIS could strategically enhance community mobilization, facilitate collaboration, and advocate for policy change.